Inflammatory Bowel Disease and Juvenile Idiopathic Arthritis: Coincidence or Connection? - Nadira Muthi Tsania; Gading Yudha Pratama; Andy Darma (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Inflammatory Bowel Disease (IBD) and Juvenile Idiopathic Arthritis (JIA) are chronic diseases characterized by persistent inflammation. The incidence of IBD in patients with JIA is higher than in the general pediatric population. The clinical manifestations of these diseases sometimes overlap or may even be absent, making early detection more difficult. This review aims to explore the pathophysiological interplay between IBD and JIA, highlighting their potential mutual influence and clinical implications. Discussion: Both IBD and JIA share a similar mechanism involving the interplay between immunological processes and environmental influences. A key common factor in both diseases is the involvement of gut microbiota. Alterations in gut microbiota can lead to gut dysfunction and immunological abnormalities. The involvement of intestinal factors in JIA pathophysiology is gaining more attention, as emerging evidence indicates a connection with the gastrointestinal system. Additionally, the use of specific medications in JIA patients has been recognized as a potential risk factor for developing IBD. Conclusion: Multiple underlying mechanisms suggest a connection between the IBD and JIA. However, additional research is needed to gain a more comprehensive understanding of this connection.